MENGURAI JARINGAN MIGRASI: KAJIAN KOMUNITAS PETANI MIGRAN BUGIS DI SULAWESI TENGGARA - Elok Mulyoutami; Ekawati Sri Wahyuni; Lala M Kolopaking (Jurnal Kependudukan Indonesia, 2014)
Spontaneous rural to rural migration have impacts on every dimension of human being, as it can lead to changes in social and family structure. These changes will be also followed by changes in livelihood, land management and decision for subsequent migration. Migration has various causes and could also resulted from cumulative causation. Study on migration network will contribute on a good portrait on continuous migration, the related actors and their roles in facilitating migration and influencing the decision for migration. Study on Buginese migrant community in Southeast Sulawesi portrays how migration network and the related actors orchestrate the migration process. Family and friendshipnetworks play a very important role in the initial process of migration. This network is also used by another central actor in the process, namely migrant broker and land broker, who become the node on the network as well as open the network to different villages and families.